2022-RA-1376-ESGO Introduction of care bundle in vulval cancer. (20th October 2022) - AlWahaibi, Fatma Mohamed; Agnew, Heather; Umeanozie, Ugochukwu; Harley, Ian; Dobbs, Stephen; Nagar, Hans; Craig, Elaine; McComiskey, Mark
Abstract : Introduction/Background: Surgery for vulvar cancer (VC) is associated with high morbidity. Design of 'care bundle' of clinical interventions would likely improve peri-operative outcomes. Aim of the study was to identify and quantify morbidity and mortality associated with VC surgeries. These data would be taken forward, after implementation of the care bundle, as baseline for comparison as to the efficacy of the intervention. Literatures and guidelines review will be undertaken to assist with the construction of the care bundle. Methodology: Patients who underwent curative surgery for VC from 2017–2018 at Belfast City Hospital were selected. Patients were followed up for 3 years postoperatively Results: 43patients underwent major VC surgery. Data were available for27 patients. Average age was67.2 years. Mean body mass index28.2 kg/m2. All patients had squamous cell carcinoma except one with melanoma. All were stage 1a- II. All patients received pre-operative prophylactic antibiotics. 37% received post-operative antibiotics for3–15 day. All vulvar wounds were closed using2.0 vicryland3.0 monocryl except one patient had clips. Groin wounds were closed using clips in 50% of the cases. Sentinel lymph node was used in25.9%. Regarding drains;62.4% had drain which were removed within7 days. Urinary catheter was removed within7.3 days. Laxatives were used in29.6% postoperatively. Mean hospital stay was12.1 days. Rate of readmission 14.8%, wound dehiscence11.1%, hematoma3.7%, infected lymphocyte11.1% and cellulitis22.2%. VC recurrence was 11.1% and death within the follow-up period was 22.2%. None related to surgery. Conclusion: Major VC surgeries are associated with high morbidity. Variety of strategies employed by clinicians regarding antibiotic therapy, wound closure, drains, urinary catheter and laxatives. Evidence-based, team agreed selection of uniform interventions as 'care bundle' would potentially lead to standardization of care and improvement in morbidity. We will present summary of evidence pertaining to creation of such a bundle and present our initial prospective results following its implementation.